2013 IFIP Wireless Days (WD) 2013
DOI: 10.1109/wd.2013.6686540
|View full text |Cite
|
Sign up to set email alerts
|

Foresighted delayed CSIT feedback for finite rate of innovation channel models and attainable NetDoFs of the MIMO interference channel

Abstract: Channel State Information at the Transmitter (CSIT) is of utmost importance in multi-user wireless networks, in which transmission rates at high SNR are characterized by Degrees of Freedom (DoF, the rate prelog). In recent years, a number of ingenious techniques have been proposed to deal with delayed and imperfect CSIT. In this paper we consider Finite Rate of Information (FRoI) channel models (CM) introduced earlier, which captures the DoF of the channel coefficient time series. Both the block fading model a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…As mentioned in [22], the numbers of active cells and active antennas N t and N r need to be optimized to find the right channel learning/using compromise because serving more users (or having more active antennas) means a larger DoF but also larger overheads. This why for small T c , TDMA, i.e., single user MIMO, is optimal.…”
Section: E Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned in [22], the numbers of active cells and active antennas N t and N r need to be optimized to find the right channel learning/using compromise because serving more users (or having more active antennas) means a larger DoF but also larger overheads. This why for small T c , TDMA, i.e., single user MIMO, is optimal.…”
Section: E Numerical Resultsmentioning
confidence: 99%
“…In [22] net DoF of proper schemes were evaluated. Here we are interested in evaluating the net DoF of the two decomposition schemes, especially because of the robustness of ergodic IA to FB delay that was recently discovered and could bring net DoF gains.…”
Section: Introductionmentioning
confidence: 99%
“…To carry out this Tx/Rx design in a distributed fashion, global CSIT is required at all BS [2]. The overhead required for this global distributed CSIT is substantial, even if done optimally, leading to substantially reduced Net DoF [3]. In [4] the simplified SIMO uplink (UL) problem with only CSIR acquisition is considered and it is shown that it is impossible to maintain any positive Net DoF if one wants to design a cellular network that extends infinitely far (the problem arises already at a finite network size that depends on the Doppler bandwidth).…”
Section: Introductionmentioning
confidence: 99%